GECCo - German-English contrasts in cohesion: insights from corpus-based studies of languages, registers and modes - Kunz, Kerstin; Lapshinova-Koltunski, Ekaterina; Martínez Martínez, José Manuel; Menzel, Katrin; Steiner, Erich (Trends in linguistics, 2021)
Frontmatter -- Acknowledgements -- Contents -- List of Tables -- List of Figures -- 1 Introduction -- 2 Conceptual clarification of cohesion -- 3 Methods for the contrastive investigation of cohesion -- 4 Systemic comparison -- 5 Assumptions and hypotheses -- 6 Corpus linguistic comparison -- 7 Contrastive summary -- 8 Implications for teaching -- 9 Discussion and outlook -- Bibliography -- Index